Inovasi Layanan E-Smart Buku Pemilik Kendaraan Bermotor (Bpkb) Ditlantas Polda Jatim Guna Meningkatkan Pelayanan Prima Di Samsat Manyar Surabaya Timur - Muh. Irvan Nur Syaifulloh; Drs. Basuki Nugroho, M.Si (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2020)
The condition of society today have increased where society are more courageous to express their aspirations, needs and demands to government toward better public service delivery. As an effort to improve the quality of public services, the government has taken various ways continuously for improvement of public services in order tomake first-rate realization of public services. One effort to improve the quality of public services is to do public service innovation. As an effort to improve the public service, Direktur Lalu Lintas Polda Jawa Timur launched an innovation called Inovasi E-Smart BPKB. The writer uses attributes of innovation theory from Evert. The results showed that the implementation of Smile Police innovation has not only relative advantage, compabillity, triabillity and observabillity but also complexity. The driving factors of E-Smart BPKB innovation are political push, economic pressure and increased efficiency and pressure to improve services, while the inhibiting factors are the excessive dependence on high performer, technology exists but inihibited by cultural and organizational barriers, and no rewards or incentives. The writer suggests to held sustainable socialization with the right target, recruit outsourced employees with expertise in IT, build cooperation with new partners and give awards or incentives to the members represented E-Smart BPKB